2020
DOI: 10.3758/s13415-020-00829-x
|View full text |Cite
|
Sign up to set email alerts
|

Exploring approach motivation: Correlating self-report, frontal asymmetry, and performance in the Effort Expenditure for Rewards Task

Abstract: Frontal EEG asymmetry has been investigated as a physiological metric of approach motivation, with higher left frontal activity (LFA) suggested to reflect approach motivation. However, correlations between LFA and traditional metrics of approach motivation (e.g., scores from the behavioral inhibition system/behavioral approach system [BIS/BAS] survey) are inconsistent. It is also not clear how LFA correlates to approach motivation on an observable, behavioral level. Here, we tested correlations between BIS/BAS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 65 publications
1
4
0
Order By: Relevance
“…Overall, these findings raise further questions about the existence and magnitude of such links, supporting studies not replicating them [22,25,26]. In particular, some correlations in previous work as well as Study 1 may have been overestimated due to random sampling error.…”
Section: Reliability and Validity Of The Original And Modified Versio...supporting
confidence: 57%
See 2 more Smart Citations
“…Overall, these findings raise further questions about the existence and magnitude of such links, supporting studies not replicating them [22,25,26]. In particular, some correlations in previous work as well as Study 1 may have been overestimated due to random sampling error.…”
Section: Reliability and Validity Of The Original And Modified Versio...supporting
confidence: 57%
“…parents and their children that symptoms of psychopathology correlated with reduced effort allocation within the EEfRT. The EEfRT has also gained evidence on a neurophysiological level, as it has been shown to be related to left-frontal cortical asymmetry in the resting state as well as during task performance [26,40], which is believed to be a neural signature of approach motivation. Moreover, Huang et al [41] found that the percentage of hard-task-choices was directly linked to the activity of the NAcc, which is a key structure of the human reward circuit, in both patients with schizophrenia and healthy participants.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the EEG proves useful for providing insights into the brain's electrical activity, and allows the evaluation of the potential load and mental effort needed for decision-making processes, through the analysis of the functional meaning of the different frequency bands (delta, theta, alpha, and beta band) [16,22]. Indeed, changes in the theta band could be associated with cognitive control and the monitoring of one's actions [23], as well as in the processing of emotional responses [24].…”
Section: Introductionmentioning
confidence: 99%
“… 42 However, self-control and grit are required to be adjunct to these reward drives for final achievement. 32 , 43 , 44 BAS sensitivity is supposed to make people prone to impulsivity and respond to short-term rewards, which may increase the risk of substance or behavioral addiction. 30 In addition, grit is supposed to entail dedication to long-term rewarding goals.…”
Section: Introductionmentioning
confidence: 99%